Carotenoid metabolomic and transcriptomic analyses provide insights into the flower color transition in Lonicera macranthoides - Ling Ling Lv; Li Yun Li; Jian Hui Pi (BMC Biotechnology)
Abstract Background In Lonicera macranthoides (L. macranthoides), the role of carotenoids in the flower color transition remains unclear. In this study, at the four flower developmental stages of green flower bud (GB), white flower bud (WB), white flower (WF) and golden flower (GF) in L.macranthoides, combined transcriptomic and carotenoid metabolomic analyses was performed to clarify the changes of carotenoid content and the expressions of genes related to carotenoid biosynthesis. Results A total of sixteen carotenoids, including 5 carotenes and 11 xanthophylls, were detected and quantified from the all samples. The content of 16 carotenoids was found to decrease first and reach the lowest level at WF, then dramatically increase at GF. At GB, the carotenoid content was the highest and the top three carotenoids in content were lutein, zeaxanthin and violaxanthin. At WB and WF, the carotenoid contents were relatively low, and the buds or flowers appeared white. At GF, β-carotene and violaxanthin were obviously dominant, accounting for 64.95% of the content of 14 detectable carotenoids, and they might be the major contributors to yellow color at GF. The expressions of differentially expressed genes indicated that with the development of flowers, the biosynthesis of carotenoids shifted from α-carotene branch to β-carotene branch. Conclusion The findings are beneficial to genetic improvement of varieties in L.macranthoides by increasing the carotenoids content in flowers.